1998
DOI: 10.1046/j.1432-1327.1998.2560388.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of two actin depolymerizing factors (ADF/cofilins) on actin filament turnover : pH sensitivity of F‐actin binding by human ADF, but not of Acanthamoeba actophorin

Abstract: Actin depolymerizing factor (ADF) from vertebrates and actophorin from Acanthamoeba castellanii are members of a protein family that bind monomeric and polymeric actin and have been shown by microscopy to sever filaments. Here, we compare the properties of recombinant human ADF and actophorin using rabbit muscle actin. ADF binds tenfold more strongly than actophorin to monomeric actin (G‐actin)‐ATP, and both bind co‐operatively to F‐actin. ADF decorates filaments below pH 7.3 and induces substantial depolymeri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
150
0
4

Year Published

1999
1999
2005
2005

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 129 publications
(166 citation statements)
references
References 41 publications
12
150
0
4
Order By: Relevance
“…In some trichomes and stomatal guard cells, we observed complete disruption of the actin cytoskeleton as a consequence of AtADF1 overexpression. These findings are consistent with the ability of ADF proteins to stimulate F-actin depolymeriza- tion, which was predicted based on in vitro studies (Carlier et al, 1997;Maciver et al, 1998;Moriyama and Yahara, 1999), and also with the results of experiments in which the levels of ADF proteins were increased in single cells by microinjection (Nagaoka et al, 1995;Hussey et al, 1998) or transient transformation (Aizawa et al, 1996;Dong et al, 2001).…”
Section: Atadf1 Proteins Appear To Control the Disassembly Of Actin Csupporting
confidence: 87%
“…In some trichomes and stomatal guard cells, we observed complete disruption of the actin cytoskeleton as a consequence of AtADF1 overexpression. These findings are consistent with the ability of ADF proteins to stimulate F-actin depolymeriza- tion, which was predicted based on in vitro studies (Carlier et al, 1997;Maciver et al, 1998;Moriyama and Yahara, 1999), and also with the results of experiments in which the levels of ADF proteins were increased in single cells by microinjection (Nagaoka et al, 1995;Hussey et al, 1998) or transient transformation (Aizawa et al, 1996;Dong et al, 2001).…”
Section: Atadf1 Proteins Appear To Control the Disassembly Of Actin Csupporting
confidence: 87%
“…9), produces the change in filament twist by increasing the angle of rotation between each longitudinally associated actin. The high degree of cooperation evident in the binding of ADF-cofilins to F-actin (20,21,25) has been explained by the changed twist they induce in the filament (25). We propose that in opening up a space between two subunits at one side of the filament, this also places a strain on the opposite Inset, the interaction is detected from fluorescence polarization measurements.…”
Section: Involvement Of Actin Subdomain 1 In the Interaction Withmentioning
confidence: 84%
“…Cofilin can be cross-linked to residues 1-12 on actin (58), and ADF can be cross-linked to cysteine 374 on actin (58). Also many have found that various fluorescent labels on cysteine 374 are quenched by ADF-cofilin binding (6,9,15,21,24,66).…”
Section: Involvement Of Actin Subdomain 1 In the Interaction Withmentioning
confidence: 99%
See 1 more Smart Citation
“…G-actin in the neutrophil is sequestered by either profilin (33) or thymosin-␤4 (34). Profilin, a nucleotide exchange factor (35,36), recovers the ADP-bound actin after its release during cofilin-assisted severing of F-actin filaments (37). Profilin mediates the formation of ATP-actin, which is then added to free F-actin barbed ends (38).…”
Section: Changing Substrate Concentration Sequestering G-actin With Lmentioning
confidence: 99%